Effects of home-based integrated sensory stimulation program to preterm infants on parents’ depression and anxiety: a randomized controlled trial - Wenjing Zheng; Rassamee Chotipanvithayakul; Thammasin Ingviya; Fang Guo (Global Health Action)
Background Preterm parents face higher risks of postpartum depression and anxiety, affecting bonding and infant development. Sensory stimulation shows promise, but its long-term impact on parental mental health needs further study. Objectives This study aimed to evaluate whether a home-based integrated sensory stimulation program, administered to preterm infants by their parents, could alleviate parental mental health issues and enhance maternal bonding and parenting competence. Methods The program, including tactile, auditory, visual, gustatory, and olfactory stimuli, was assessed in a block-randomized controlled trial from November 2018 to January 2020. A total of 200 parents of preterm infants were recruited, and the intervention continued at home until the infants reached six months corrected age. Parents’ depression and anxiety were assessed using validated scales at baseline, and at first, third, and sixth month follow-ups. Results The intervention group included 98 parents, and the control group comprised 102 parents. At the six-month follow-up, the intervention group demonstrated significant improvements in maternal depression, state anxiety, and trait anxiety compared to the control group. In the mixed linear model, the intervention was associated with reductions in maternal trait anxiety (d =-2.18; 95% CI: −4.30, −0.06), paternal trait anxiety (d =-3.37; 95% CI: −5.62, −1.11) and state anxiety (d =-4.63; 95% CI: −7.00, −2.26). Conclusion The home-based integrated sensory stimulation program, when provided by parents to preterm infants, was effective in improving parents’ mental health and can serve as an alternative treatment for postpartum depression and anxiety in parents of preterm infants at home.